The Demand for Simple-sum and Divisia Monetary Aggregates for Pakistan: A Cointegration Approach (The Pakistan Development Review, 1997)
Financial liberalisation and the advance of financial innovation in a number of developed economies has been blamed for the break-down in the demand for money based on simple sum measures. This break-down has prompted research into Divisia measures of the demand for money. Like many developing countries, Pakistan is going through a period of financial deregulation which goes hand in hand with financial innovation due to increased competition in the banking industry. This paper employs the methodology of cointegration to compare simple-sum and Divisia level estimates of the demand for money for Pakistan for the period 1974Q4 to 1992Q4. Simple sum measures of M1 and M2 were compared with Divisia versions. The paper reports little evidence in support of the superiority of the Divisia monetary aggregates. Both types of measure produce a stable demand for money and perform satisfactorily in post-sample stability tests, although the Divisia measure appears to perform marginally better on conventional statistical criteria. However, our conclusions have to be qualified by the limitations of the data and the knowledge that the period of financial innovation and deregulation has been relatively recent. The policy significance of the results suggests that currently there is no advantage from switching from simple-sum to Divisia aggregates at the existing level of official aggregation as the proper indicator of monetary policy. However, if financial deregulation and innovation continues at the current pace, the Divisia aggregates may in future prove to be the better indicator.